1998
DOI: 10.1002/(sici)1097-0126(199811)47:3<295::aid-pi7>3.3.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic oxidative polymerization of 4-hydroxybenzoic acid derivatives to poly(phenylene oxide)s

Abstract: : Enzymatic oxidative polymerization of 4-hydroxybenzoic acid derivatives using oxidoreductases has been carried out in an aqueous organic solvent at room temperature under air. The monomers used in this study were 4-hydroxybenzoic acid, 3,5-dimethoxy-4-hydroxybenzoic acid (syringic acid) and 3,5-dimethyl-4-hydroxybenzoic acid. The latter two monomers were subjected to oxidative polymerization using horseradish peroxidase (HRP), which involved elimination of carbon dioxide and hydrogen from the monomer to prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 0 publications
5
48
0
1
Order By: Relevance
“…10. The findings that the polymer is composed of oxyphenylene units is consistent with literature results on the enzymatic polymerization of phenolic monomers (Aktas et al, 2003;Ikeda et al, 1998;Marjasvaara et al, 2006). In consequence of the C-O-C coupling, the synthetic polymer can not be regarded as a fully conjugated system.…”
Section: Methylene and Carboxylic Groupssupporting
confidence: 90%
“…10. The findings that the polymer is composed of oxyphenylene units is consistent with literature results on the enzymatic polymerization of phenolic monomers (Aktas et al, 2003;Ikeda et al, 1998;Marjasvaara et al, 2006). In consequence of the C-O-C coupling, the synthetic polymer can not be regarded as a fully conjugated system.…”
Section: Methylene and Carboxylic Groupssupporting
confidence: 90%
“…Another interesting example is the polymerization of p-hydroxy benzoic acid (derivates), which proceeds highly regioselectively producing oxyphenylene connections exclusively (Figure 14) [95]. Polymerization of catechols and hydroquinones can be tedious due to facile oxidation to the corresponding quinones.…”
Section: Substrate Engineeringmentioning
confidence: 99%
“…4 Recently, it has been found that oxidoreductases (HRP, SBP, and laccases) induce the oxidation polymerization of 4-hydroxybenzoic acid derivatives in an aqueous organic solvent at room temperature under air to give a PPO in good yields (Scheme 16). 80 or laccase/O 2 system, liberating carbon dioxide during the reaction. Monomer a did not polymerize.…”
Section: Synthesis Of Poly(phenylene Oxide)smentioning
confidence: 99%